Two Novel Lyso-Ornithine Lipids Isolated from an Arctic Marine Lacinutrix sp. Bacterium - Kristoffersen, Venke; Jenssen, Marte; Raid Jawad, Heba; Isaksson, Johan; Hansen, Espen; Rämä, Teppo; Østnes Hansen, Kine; Andersen, Jeanette Hammer (Molecules, 2021)
The Lacinutrix genus was discovered in 2005 and includes 12 Gram-negative bacterial species. To the best of our knowledge, the secondary metabolite production potential of this genus has not been explored before, and examination of Lacinutrix species may reveal novel chemistry. As part of a screening project of Arctic marine bacteria, the Lacinutrix sp. strain M09B143 was cultivated, extracted, fractionated and tested for antibacterial and cytotoxic activities. One fraction had antibacterial activity and was subjected to mass spectrometry analysis, which revealed two compounds with elemental composition that did not match any known compounds in databases. This resulted in the identification and isolation of two novel isobranched lyso-ornithine lipids, whose structures were elucidated by mass spectrometry and NMR spectroscopy. Lyso-ornithine lipids consist of a 3-hydroxy fatty acid linked to the alpha amino group of an ornithine amino acid through an amide bond. The fatty acid chains were determined to be iso-C15:0 (1) and iso-C16:0 (2). Compound 1 was active against the Gram-positive S. agalactiae, while 2 showed cytotoxic activity against A2058 human melanoma cells.